Risk factors for respiratory syncytial virus hospitalisation in children with heart disease. Issue 10 (18th June 2009) - Kristensen, K; Stensballe, L G; Bjerre, J; Roth, D; Fisker, N; Kongstad, T; Svendsen, A L; Nielsen, B W
Abstract : Objective: To assess the risk and risk factors for respiratory syncytial virus (RSV) hospitalisation and determinants of the severity of RSV disease in children with heart disease. Methods: By using a database on RSV tests in Denmark all children with RSV diagnosed with heart disease in Denmark from January 1996 to April 2003 were identified. For each case child one control child matched for age and centre was drawn from the population of children with heart disease. Clinical information was obtained through a review of all records. Results: Data were obtained on 313 pairs. Median age at admission was 280 days (range 15–2379). In the multivariate analysis predictors of RSV hospitalisation were Down syndrome (odds ratio (OR) 3.24, 95% CI 1.80 to 5.80), cardiomyopathy (OR 5.84, 95% CI 1.26 to 27.16) and haemodynamically significant heart disease (OR 1.53, 95% CI 1.04 to 2.26). During RSV hospitalisation predictors of the need for respiratory support (supplemental oxygen, nasal continuous positive airway pressure or mechanical ventilation) were young age (relative risk (RR) 0.47, 95% CI 0.32 to 0.67 per additional year of age) and cardiac decompensation (RR 1.81, 95% CI 1.02 to 3.23). The incidence rate of RSV hospitalisation among children with any heart disease aged 0–23 months was 5.65 per 100 child-years. Conclusion: In children with heart disease risk factors for RSV admission are Down syndrome, cardiomyopathy and haemodynamically significant heart disease. Young age and cardiac decompensation are associated with a more severe course of RSV disease.